Evaluation of the Fixation Method and the Intraperitoneal Mesh Location Effect on Adhesion Formation, Deformation, and Shrinkage of the Mesh in Large Animals - V. P. Armashov; A. M. Belousov; P. А. Potapov; N. L. Matveev (Инновационная медицина Кубани, 2023)
Background: The quality of mesh integration and adhesion formation in the intraperitoneal onlay mesh hernia repair (IPOM) is considered to depend not only on the mesh structure but also on a complex of other factors. This study aims to evaluate the correlation between the adhesion formation, mesh deformation, and shrinkage on the fixation method and the mesh location in the abdominal cavity.Materials and methods: During laparoscopy (IPOM), 6 different meshes (2 each in the epi-, meso-, and hypogastric regions) were installed in the intraperitoneal position in each of 3 pigs. For mesh fixation, absorbable poly-D, L-lactide or non-absorbable stainless steel and polyetheretherketone (PEEK) tacks were randomly selected. Relaparoscopy was performed after 45 days, autopsy after 90 days. The results were calculated for meshes with absorbable and non-absorbable tacks and for meshes placed in the epi-, meso-, and hypogastrium.Results: The fixation methods did not significantly affect the deformation and shrinkage of the mesh. Absorbable tacks were associated with higher adhesion formation for most indicators at all stages of the study. The difference between absorbable and non-absorbable fixation reached a maximum by day 90, when the number of mesh pieces with adhesions was 66.7% vs 11.1% (P = .05), and the adhesion scores were 5 (0-6) vs 0 (0-0) (P = .01). The mesh location on the abdominal wall did not significantly affect its deformation and shrinkage. At the same time, most of the adhesion indicators depended on the mesh location. Starting from hypogastrium, the extent and the type of adhesions increased and were maximal in epigastrium. The greatest difference between the epi-, meso-, and hypogastrium was noted by day 45, when the number of mesh pieces with adhesions was 100%, 50%, and 16.7% (P = .014), and the adhesion scores were 6 (5-7), 2 (0-4), and 0 (0-0) (P = .007).Conclusions: The fixation method and the intraperitoneal mesh location do not affect its deformation and shrinkage but significantly affect the adhesion formation.